Pengaruh disiplin, mutasi dan penempatan terhadap kinerja Pegawai Negeri Sipil di Sekretariat Daerah Kabupaten Badung - Agus Glanar Cahyana; Nyoman Diah Utari Dewi; Anak Agung Gede Raka; Luh Rahayu Rinitu (Penerbit Goodwood, 2023)
Purpose: The aim of this study is to analyze the influence of discipline, transfer, and placement on employee performance at the Badung Regency Regional Secretariat. Method: This research methodology was quantitative. A total of 78 samples were analyzed. Sampling was performed using a random method. Data collection uses questionnaires. Result: The results of the research show there is a positive influence between discipline (X1) on employee performance (Y), a positive influence of mutation (X2) on employee performance (Y), a positive influence between placement (X3) on employee performance (Y). This means that discipline (X1), transfer (X2), and placement (X3) simultaneously had a significant (real) influence on employee performance (Y). The results show that if employee discipline is simultaneously improved, specifically transfers, and the suitability of employees placed with their jobs, the performance of Badung Regency Regional Secretariat employees will be higher. Leaders should conduct periodic performance evaluations, develop clear transfer policies, and assign employees according to their needs. Limitations: The sample used in this research was a saturated sample of 78 ASN employees at the Badung Regency Regional Secretariat, so the possibility of obtaining different results cannot be ruled out if a research model and a larger number of samples were used. Contribution: This research is expected to provide additional information or input to improve the performance of ASN employees at the Badung Regency Regional Secretariat.